208k views
5 votes
Triangle ABC was transformed to create triangle A'B'C'.

Which rule best describes this transformation?

Responses

(x, y) → (x, y - 7)
(x, y) → (x, y - 7)

(x, y) → (x, -y)
(x, y) → (x, -y)

(x, y) → (x - 7, y)
(x, y) → (x - 7, y)

(x, y) → (-x, y)
(x, y) → (-x, y)
Skip to navigation

Triangle ABC was transformed to create triangle A'B'C'. Which rule best describes-example-1
User Sumrak
by
5.0k points

1 Answer

1 vote

Answer: (x, y) → (x, y - 7)

Explanation:

User Paulek
by
5.7k points